Mycobacterioses in dogs and cats from Buenos Aires, Argentina - Barandiaran, Soledad; Martinez Vivot, Marcela; Falzoni, Elvira; Marfil, Maria Jimena; Perez Tort, Gabriela; Rovatti, Paula; Fernandez, Mónica; Iachini, Ricardo; Satek, Fernanda; Duchene, Adriana; Zumarraga, Martin Jose (Sage Publications, 2020)
Mycobacterioses can produce nonspecific clinical signs in dogs and cats that make diagnosis difficult. Furthermore, the full characterization of mycobacterial agents is not always possible or practical. We characterized mycobacteria detected through cytology in 12 dogs and 7 cats with generalized clinical signs from the province of Buenos Aires in Argentina. In dogs, molecular testing confirmed the presence of Mycobacterium avium subsp. hominissuis (MAH) in 8 cases and M. fortuitum in 1 case. All dogs were Miniature Schnauzers, suggesting that this breed may be more susceptible to M. avium than other dog breeds. The cat isolates were 2 M. bovis, 1 M. fortuitum, and 1 MAH. Mycobacterial interspersed repetitive unit–variable-number tandem repeat patterns suggested possible links with cattle, swine, and humans studied previously in Argentina. The results show that pets may act as susceptible hosts with the potential risk of transmitting the infection to humans and other animals.